New record of leaf galls on Grey Mangrove induced by gall midges (Diptera, Cecidomyiidae) in New Caledonia - Ayman Khamis Elsayed; Christian Gilbert Mille; Atsushi Kawakita (Check List)
A heavy infestation of leaf galls formed by a gall midge (Diptera, Cecidomyiidae) species was recently discovered on Grey Mangrove, Avicennia marina subsp. australasica (Walp.), in New Caledonia. In this study, we identify the gall midge as belonging to the genus Actilasioptera Gagné, 1999 and a potentially closely related species to the Australian Actilasioptera coronata Gagné, 1999. While the two species seem morphologically similar, differences in gall shapes suggest the need for further morphological examination and molecular comparison. Notes on life history traits and distribution are given, along with photographs of galls, larvae, pupae, and a female specimen.